Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858169
|View full text |Cite
|
Sign up to set email alerts
|

WearWrite

Abstract: The physical constraints of smartwatches limit the range and complexity of tasks that can be completed. Despite interface improvements on smartwatches, the promise of enabling pro ductive work remains largely unrealized. This paper presents WearWrite, a system that enables users to write documents from their smartwatches by leveraging a crowd to help trans late their ideas into text. WearWrite users dictate tasks, re spond to questions, and receive notifications of major edits on their watch. Using a dynamic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…In prior projects within this theme, crowd-powered systems have not always performed better than users. In WearWrite (Nebeling et al, 2016), Chorus (Lasecki et al, 2013b), and Knowledge Accelerator Chang et al, 2016), the proposed solutions did not necessarily produce results that were faster or of higher quality than traditional methods. The value of these projects was opening up new possibilities of completing tasks in ways that were not possible before, especially with respect to flexibility.…”
Section: Assessing Performance and Goal Achievementmentioning
confidence: 94%
“…In prior projects within this theme, crowd-powered systems have not always performed better than users. In WearWrite (Nebeling et al, 2016), Chorus (Lasecki et al, 2013b), and Knowledge Accelerator Chang et al, 2016), the proposed solutions did not necessarily produce results that were faster or of higher quality than traditional methods. The value of these projects was opening up new possibilities of completing tasks in ways that were not possible before, especially with respect to flexibility.…”
Section: Assessing Performance and Goal Achievementmentioning
confidence: 94%
“…Text-entry for smartwatches is a challenge due to the small screen size, and research has examined novel screen keyboards such as Fleksy and Swype [5], by optimising the text layout [6], but also whether voice could be used instead of keyboards, e.g. WearWrite [34]. There has also been an investigation of miniature QWERTY keyboards with zoom function to assist in typing on smartwatches [29], amongst other proof-of-concept studies for text entry interaction.…”
Section: Smartwatch Text Inputmentioning
confidence: 99%
“…Some even enable collaborative, decentralized coordination instead of step-by-step instructions [46,86]. As the area advanced, it began to make progress in achieving significantly more complex and interdependent goals [43], such as knowledge aggregation [30], writing [43,61,78], ideation [84,85], clustering [12], and programming [11,50].…”
Section: Crowdsourcing Workflowsmentioning
confidence: 99%
“…Recent work instead sought to achieve complex goals by moving from microtask workers to expert workers. Such systems now support user interface prototyping [70], questionanswering and debugging for software engineers [11,22,50], worker management [28,45], remote writing tasks [61], and skill training [77]. For example, flash teams demonstrated that expert workflows can achieve far more complex goals than can be accomplished using microtask workflows [70].…”
Section: Crowdsourcing Workflowsmentioning
confidence: 99%